Human Resource Development in Asia: Achievements and Tasks Ahead - K. L. Luthra (Asian Development Review, 1984)
Improving the health and level of education of a country’s population is both a means and an end of economic development. The importance of human resource development as a means of promoting economic growth is now well acknowledged, and developing countries have been allocating large amounts of resources to education and health programs. This has led to improvements: literacy rates are going up with the extended provision of schooling, crude death rates are declining as a result of better health services, and life expectancy is improving…